Venom Insulins of Cone Snails Diversify Rapidly and Track Prey Taxa. (14th August 2016) - Safavi-Hemami, Helena; Lu, Aiping; Li, Qing; Fedosov, Alexander E.; Biggs, Jason; Showers Corneli, Patrice; Seger, Jon; Yandell, Mark; Olivera, Baldomero M.
Abstract: A specialized insulin was recently found in the venom of a fish-hunting cone snail, Conus geographus . Here we show that many worm-hunting and snail-hunting cones also express venom insulins, and that this novel gene family has diversified explosively. Cone snails express a highly conserved insulin in their nerve ring; presumably this conventional signaling insulin is finely tuned to the Conus insulin receptor, which also evolves very slowly. By contrast, the venom insulins diverge rapidly, apparently in response to biotic interactions with prey and also possibly the cones' own predators and competitors. Thus, the inwardly directed signaling insulins appear to experience predominantly purifying seleto target an internal receptor that seldom changes, while the outwardly directed venom insulins frequently experience directional selection to target heterospecific insulin receptors in a changing mix of prey, predators and competitors. Prey insulin receptors may often be constrained in ways that prevent their evolutionary escape from targeted venom insulins, if amino-acid substitutions that result in escape also degrade the receptor's signaling functions.